Quality of the surface texture and mechanical properties of FDM printed samples after thermal and chemical treatment - Kozior, Tomasz (Strojniški vestnik, 2020)
Additive manufacturing technologies are nowadays used in various industries. In most cases, however, the surface texture of the produced models is unsatisfactory and requires further processing, aiming to reduce surface roughness and waviness. The quality of the surface layer in many cases plays not only an aesthetic role but also affects, for example, the process of wear and tribological properties. In the presented work, samples prepared by fused deposition modelling technology from polylactic acid (PLA) material were subjected to tests. The samples were subjected to heat or chemical treatment through the use of acetone. The quality of the surface texture was tested both before and after the treatments. In addition, tests were carried out to determine the effect of the presented finishing treatment on the tensile strength of the tested sample models. The test results showed that both thermal treatment and acetone treatment influence the surface texture quality, especially the waviness, and that the acetone treatment can improve some mechanical properties.
Keywords: 3D printing; 3D-tiskanje; FDM; finishing treatment; fused deposition modelling; kakovost površine; končna obdelava; mechanical properties; mehanske lastnosti; surface texture